Psychotraumatic Childhood Experiences and Anxiety in Educational Setting - Kalogeratos, Gerasimos; Anastasopoulou, Eleni; Tsagri, Angeliki; Tseremegklis, Chrysostomos; Kriparopoulou, Antigoni (Technium Education and Humanities, 2024)
This study examines the intricate relationship between childhood experiences that induce psychological trauma and the manifestation of anxiety in educational settings. An in-depth analysis is conducted on the enduring psychological consequences of childhood psychotrauma, encompassing various forms of abuse, neglect, and exposure to domestic or community violence, with a particular focus on how these factors affect the learning environments of children. The study highlights the connection between these initial negative experiences and the emergence of different anxiety disorders, which can significantly impede a student's academic performance, social interactions, and overall well-being in educational settings. The key findings suggest a strong correlation between childhood psycho-trauma and heightened levels of anxiety in educational settings. The study emphasizes the need for educators to possess heightened awareness and specialized training to detect and effectively address anxiety resulting from trauma accurately.